Pengaruh Iklim Belajar, Motivasi Belajar dan Habits Of Mind Terhadap Prestasi Belajar - Amelia, Dinda; Widyaningrum, Bakti; Srigustini, Astri (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The problem in the study is that learning achievement in school children is still low. The purpose of the study was to determine “The Effect of Learning Climate, Learning Motivation and Habit Of Mind on Learning Achievement in Economic Subjects (Survey of SMA Negeri 6 Tasikmalaya students).” The study used quantitative research with a survey method. The population in this study were students in grades XI and X of SMA Negeri 6 Tasikmalaya, totaling 647. The technique in taking this sample is using simple random sampling which amounted to 248 samples. Data collection techniques in the study using a questionnaire. The results showed that learning climate has a positive and significant effect on learning achievement, learning motivation has a positive and significant effect on learning achievement, habit of mind has a positive and significant effect on learning achievement. Simultaneously, it shows that learning climate, learning motivation and habit of mind have a positive and significant effect on learning achievement.